Thomas Aquinas' Divine Simplicity as Biblical Hermeneutic. (29th April 2019) - Long, D. Stephen
Abstract: Long draws from the Old Testament scholar Walter Brueggemann's commentary on Jeremiah some strong reasons for rejecting the traditional teaching on divine simplicity. Above all, for Brueggemann the book of Jeremiah simply will not work if God is simple: God explicitly tells Jeremiah that God suffers and also that God changes in response to Israel. According to Long, however, Thomas Aquinas's doctrine of divine simplicity actually upholds the points that Brueggemann draws from Jeremiah. Long argues that theological accounts of divine simplicity should especially have two purposes: to serve as a way of manifesting in speech the mystery of the Triune God, and to affirm God's transcendent sovereignty over creation. In light of Brueggemann's approach, Long examines four early Reformed theologians: Peter Vermigli (1499‐1562), Girolamo Zanchi (1516‐1590), John Biddle (1615‐1662) and John Owen (1616‐1683). While Biddle rejects divine simplicity, the others uphold it. Long shows that their teaching on divine simplicity focuses on God's transcendent sovereignty over creation. By contrast, Long finds Aquinas's doctrine of divine simplicity to be more helpful in upholding Brueggemann's insights, insofar as Aquinas uses the doctrine to defend the simplicity of the Triune God. Rather than focusing on God's sovereign power, Aquinas's doctrine of divine simplicity focuses on getting the Trinitarian processions right.